Investigating unusual homonuclear intermolecular “through-space” J couplings in organochalcogen systems - Camacho, P; McKay, D; Dawson, DM; Kirst, C; Yates, JR; Green, TFG; Cordes, DB; Slawin, AMZ; Woollins, JD; Ashbrook, SE (American Chemical Society, 2016)
Although the electron-mediated spin–spin or J coupling is conventionally viewed as transmitted via covalent bonds, examples of J couplings between atoms that are not formally bonded but are in close proximity (termed “through-space” J couplings) have been reported. In this work, we investigate the observation of homonuclear 31P J couplings in organochalcogen heterocycles, which occur between 31P in two separate molecules, confirming without doubt their through-space nature. The presence of this interaction is even more surprising for one compound, where it occurs between crystallographically equivalent species. Although crystallographically equivalent species need not be magnetically equivalent in the solid state, owing to the presence of anisotropic interactions, we demonstrate that it is not the shielding anisotropy that lifts magnetic equivalence, in this case, but the presence of heteronuclear couplings to 77Se. We support our experimental observations with periodic scalar-relativistic density functional theory calculations and coupling density deformation plots to visualize the mechanism of these interesting interactions.